Administrative reform - proceed with caution - Caiden, Gerald E. (1999)
The past decade has seen an acceleration in administrative reform. All around the world, the administrative state is being reexamined and reshaped. As a result, government is being transformed and reinvented, bureaucrataic centralism is being abandoned, the welfare state is being downsized, the public sector is being reduced, public organizations are being reengineered, and public management is being reinvigorated. This all sounds familiar. Governments have promised as much before but they have too often failed to improve their performance simply because many reforms have proved disappointing. Reforms have failed to make any significant impact; they have gone wrong; they have been overtaken by events. The reformers have been too optimistic and often unrealistic; they have fallen into the many traps of implementation. Magical keys to reform success are few and far between. Reforms need strong political backing, mass support, and competent inside facilitation. Reformers need to take their time and accept what they can achieve even if the results fall short of their intentions. Above all, they must not give up when the going gets tough; persistence will eventually succeed. - Reproduced
Keywords: Administrative reform